Analisis Kondisi Peralatan Unit Kerja AVSEC dalam Menunjang Keamanan dan Keselamatan Penerbangan Berdasarkan KP 139 Tahun 2018 di Bandar Udara Banyuwangi - Gunita Aulia; Djoko Widagdo (Jurnal Bisnis Kreatif dan Inovatif, 2024)
Aviation is a critical sector that requires high levels of security and safety, with regulations such as KP 139 Year 2018 in Indonesia setting operational standards for Aviation Security (AVSEC). Banyuwangi Airport, as a growing airport, must ensure that its security equipment meets these standards. This study aims to analyze the condition of AVSEC equipment at the airport, assess its compliance with regulations, and provide recommendations for enhancing aviation security and safety. This research employs a qualitative method to describe the condition of Aviation Security (AVSEC) equipment at Banyuwangi Airport and its compliance with KP 139 Year 2018. Data were collected through observation, interviews, and documentation, focusing on the validity and reliability of the data through triangulation. The study was conducted from July 20 to 26, 2024, involving sources from the AVSEC unit. The research steps included obtaining permissions, data collection, observation, interviews, and data analysis to draw conclusions.The research findings indicate that the condition of AVSEC equipment at Banyuwangi Airport reveals that some equipment, such as the X-ray Machine and Walk Through Metal Detector, requires technological upgrades, while other equipment, such as the Hand Held Metal Detector, CCTV System, and Patrolling Vehicle, functions well and meets standards. Although routine maintenance is performed, challenges related to funding and personnel training still need to be addressed. The implementation of Standard Technical Operations (STO) includes equipment feasibility assessments, standard operating procedures, personnel training and certification, as well as routine calibration and maintenance. Performance evaluations are also conducted periodically to ensure that the equipment operates optimally in supporting aviation security.